2017
DOI: 10.2217/nnm-2017-0140
|View full text |Cite
|
Sign up to set email alerts
|

Pentablock Copolymer Dexamethasone Nanoformulations Elevate MYOC: In Vitro liberation, Activity and Safety in Human Trabecular Meshwork Cells

Abstract: The treatment of HTM cells using DEX-PB-NPs were analyzed in this study. The in vitro cell-based system developed here is a valuable tool for determining the safety and effects of steroids released from polymeric NPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Details of mouse numbers in each cohort and the injected eyes are listed in Table 1 . A previous in vitro study showed that DEX release from the particles typically lasted for 3 months, with about 20% of DEX released in the first 2 days 12 .…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…Details of mouse numbers in each cohort and the injected eyes are listed in Table 1 . A previous in vitro study showed that DEX release from the particles typically lasted for 3 months, with about 20% of DEX released in the first 2 days 12 .…”
Section: Methodsmentioning
confidence: 98%
“…All PB-NPs were provided by the lab of one co-author (A.K.M.) Information regarding the synthesis of copolymers, formulation of DEX-encapsulated PB nanoparticles and in vitro drug release profile have been described in detail in a recent publication 12 . Further, the safety of both PB-NPs and DEX-PB-NPs were evaluated in in vitro cell culture system.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Steroid-induced OHT in mice was generated using nanotechnology (Agrahari, Li et al 2017), resulting in a model that closely matched steroid-induced observations in the human condition (decreased outflow facility, increased accumulation of ECM in the TM, and elevated IOP) (Johnson, Bradley et al 1990, Johnson and Knepper 1994, Johnson, Gottanka et al 1997, Clark, Steely et al 2001. The present study further highlights the utility of this mouse model of steroid-induced glaucoma and its translational relevance to the human clinical condition.…”
Section: Discussionmentioning
confidence: 99%